Aesthetic vision and German romanticism - Prager, Brad (Camden House, 2007)
The work of the groundbreaking writers and artists of German Romanticism – including the writers Tieck, Brentano, and Eichendorff and the artists Caspar David Friedrich and Philipp Otto Runge – followed from the philosophical arguments of the German Idealists, who placed emphasis on exploring the subjective space of the imagination. The Romantic perspective was a form of engagement with Idealist discourses, especially Kant's Critique of Pure Reason and Fichte's Science of Knowledge. Through an aggressive, speculative reading of Kant, the Romantics abandoned the binary distinction between the palpable outer world and the ungraspable space of the mind's eye and were therefore compelled to develop new terms for understanding the distinction between
Title from publisher's bibliographic system (viewed on 21 Apr 2017)
Keywords: Deutsch; Literatur; Ästhetische Wahrnehmung; Romantik